Introducing the World of Business to Elementary School Children - Nofeni Ramadani; Putri Dwi Rahayu; Widi Hartati; Rahmat Ramadhani; Muhammad Sofwan; Muhammad Sholeh (Universitas Pendidikan Indonesia (UPI), 2024)
In a competitive global era, it is important for elementary school children in Indonesia to understand the basics of business, creativity and entrepreneurship. This research aims to evaluate the effectiveness of business teaching methods that include the use of technology, simulation games, and entrepreneurial projects, as well as to understand the role of teacher, parent, and community support. Using a library research approach, this research collects and analyzes data from academic journals, textbooks and policy documents. The results show that the interactive teaching approach and use of technology improve students' understanding of business and develop very important soft skills such as leadership, negotiation skills, creativity, responsibility, ethics and cooperation. Apart from that, building students' character about business cannot be separated from the support and encouragement from parents and teachers who play a very important role. Suggestions from this research include developing more in-depth teacher training in business teaching, increasing parental involvement, and wider use of technology in the digital era to enrich the learning experience. This increase is expected to strengthen students' business understanding and prepare them for future economic challenges, helping them to form a proactive and entrepreneurial attitude that can benefit their future. This can ensure that business education is effectively integrated into the primary school curriculum in Indonesia.